Investigation of the Esophageal Rho-kinase Expression in Patients with Barrett's Esophagus. (21st June 2013) - Demiryürek, Seniz; Koruk, Irfan; Bozdag, Zehra; Ozkara, Esma; Kaplan, Davut Sinan; Oztuzcu, Serdar; Cetinkaya, Ali; Alasehirli, Belgin; Demiryürek, Abdullah Tuncay
Abstract: The mechanisms responsible for the malignant transformation in Barrett's esophagus (BE) are still poorly understood. The authors have evaluated the role of Rho-kinase (ROCK1 and ROCK2) expressions in patients with BE. All patients underwent upper gastrointestinal system endoscopy, which was confirmed histologically. Real-time PCR revealed no marked change in gene expressions of ROCK1 and ROCK2 at mRNA levels in BE when compared to controls. Immunohistochemical and western blot analyses showed no change in ROCK1 and ROCK2 protein expressions in BE. This study demonstrates that Rho-kinase gene and protein expressions are not modified in BE.